Stage IIIa cancer of the right lung ingrowing via right lower pulmonary vein to the left heart atrium - Błasiak, Piotr; Kwinecki, Paweł; Kacprzak, Grzegorz; Pawełczyk, Konrad; Marciniak, Marek; Winter, Małgorzata; Rzechonek, Adam (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Computed tomography is performed in every patient before lung tumour resection. The presented case realises how important it is to perform this study with contrast. In a 75-year-old male we detected a tumour ingrowing from the right lung through the right lower pulmonary vein into the left atrium of the heart. The patient was qualified for primary sternotomy with extracorporeal circulation and resection of the intracardiac part of the tumour. In the second stage, right-sided thoracotomy was performed, and right lower lung lobectomy was done. Mixed heterogeneous lung cancer was diagnosed (squamous cell and non-small cell endocrine) in stage IIIa. The perioperative period was uncomplicated. The patient, due to renal failure, was not eligible for adjuvant chemotherapy. If the patient were qualified for lobectomy based directly on computed tomography without contrast, there would have been a high risk of perioperative death due to embolic incidents and heart failure. Effective multidisciplinary collaboration allowed us to avoid this sort of complication.